2021
DOI: 10.1016/j.ihj.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel predictors and adverse long-term outcomes of No-reflow phenomenon in patients with acute ST elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: Objectives The no-reflow phenomenon occurs in 25% of patients with ST elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI), and may be associated with adverse outcomes. The aim of our study was to detect novel predictors of no-reflow phenomenon and the resulting adverse long term outcomes. Methods We enrolled 400 STEMI patients undergoing primary PCI; 228 patients had TIMI flow 3 after PCI (57%) and the remaining 172 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
3
19
1
3
Order By: Relevance
“…This study showed that admission EF was significantly lower among No Reflow Group. This was in line with Refaat et al (13) who reported that the incidence of no reflow was associated with decreased LVEF on admission (P < 0.001).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study showed that admission EF was significantly lower among No Reflow Group. This was in line with Refaat et al (13) who reported that the incidence of no reflow was associated with decreased LVEF on admission (P < 0.001).…”
Section: Discussionsupporting
confidence: 91%
“…We found that no reflow group significantly associated with Patients with Killip classes 3 and 4 Refaat et al (13) confirmed this finding.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, He et al (29), revealed that clinical the SYNTAX score applied grouping patients by risk status for very long-term adverse clinical outcomes undergoing PCI and that predictive precision for 2-year all-cause mortality were improved using the clinical SYNTAX score. There are studies in the literature that demonstrated No-reflow was associated with increased allcause mortality in patients with acute myocardial infarction (30,31). Our study reported comparable findings.…”
Section: Discussionsupporting
confidence: 86%